2016
DOI: 10.1049/el.2015.3682
|View full text |Cite
|
Sign up to set email alerts
|

Energy harvesting and information processing in two‐way multiplicative relay networks

Abstract: An energy harvesting (EH) and information processing network based on two-way multiplicative relay is proposed. In the proposed scheme, two nodes communicate with each other via an energy constrained multiplicative relay node. The relay node uses power splitting-based relaying protocol for EH and information processing. The numerical results show that the proposed scheme outperforms the legacy amplify-and-forward EH relaying technique.Introduction: Radio frequency (RF) energy harvesting (EH) is a promising tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 6 publications
0
40
0
Order By: Relevance
“…. Substituting (10), (11), (12) and (18) (or (19), or (20), or (21), or 0) into (8) and (7), P S out is determined. The system outage capacity τ S out is given as…”
Section: B System Outage Probabilitymentioning
confidence: 99%
“…. Substituting (10), (11), (12) and (18) (or (19), or (20), or (21), or 0) into (8) and (7), P S out is determined. The system outage capacity τ S out is given as…”
Section: B System Outage Probabilitymentioning
confidence: 99%
“…Note that no power has been allocated to the channels whose index is higher than * . On the other hand, power levels for channels whose index is lower than * are determined according to (23), where * , is added with the difference of step depth of corresponding step and * th step.…”
Section: Geometric Water-filling Based Optimal Transmit Powermentioning
confidence: 99%
“…A two-way relay network based on the denoise-andforward relay with noncoherent differential binary phaseshift keying modulation has been studied in [22], while an energy harvesting and information processing network based on two-way multiplicative relay using PSR protocol was investigated in [23]. The numerical results showed that the proposed scheme outperforms the amplify-and-forward EH relaying technique.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the TS receiver, three wireless power transfer policies have been proposed to maximize the capacity [9]. A static equal PS scheme has been developed to maximize the overall outage capacity for three-step AF TWRNs [10], where the PS ratio is determined by the statistical channel state information (CSI). The outage capacity can be improved by adopting a dynamic PS scheme, because the PS ratio can be adaptive to the instantaneous CSI instead of to the statistical CSI.…”
Section: Introductionmentioning
confidence: 99%